Ulkussuche mit 99mTc-Sucralfat - Tietze, P.; Gratz, K. F.; Freise, J.; Hundeshagen, H. (Nuklearmedizin - NuclearMedicine, 1988)
Sucralfate is an agent commonly used in the therapy of gastrointestinal ulcers. It binds itself to proteins in the ulcer crater. A selective labeling with pure 99mTc-pertechnetate is possible. For an unequivocal ulcer localization or exclusion, images have to be taken in the upright and supine positions. Encouragement of gastric emptying is useful. Images should be taken at least twice, the last one 4 h after ingestion. The method might be used when endoscopy is difficult, incomplete or contraindicated, and for follow-up during therapy. We recommend it also in the search for the cause of intermittent bleeding.